Fuel Conversion and CO2 Selectivity Improvement by Adding other Oxygen Carrier for Syngas Chemical Looping Combustor at High Temperature Condition. (July 2017) - Ryu, Ho-Jung; Park, Young Cheol; Lee, Seung-Yong; Shun, Dowon; Baek, Jeom-In
Abstract: Chemical-looping combustion (CLC) is a novel combustion technology with inherent separation of the greenhouse gas CO2 and no NOx emission. The chemical-looping combustor consists of two reactors, an oxidation reactor and a reduction reactor. A fuel and an air go through the different reactors. However, fuel conversion and CO2 selectivity in the reduction reactor decreased as the reaction temperature increased within high temperature range (>900̊C due to the increment of exhaust CO concentration from reduction reactor in case of NiO based particle was used as an oxygen carrier in a chemical looping combustion system. To improve reduction reactivity at high temperature range, the applicable metal oxide component was selected by calculation of the equilibrium CO concentrations of metal oxide components at high temperature range. Feasibility of reduction reactivity improvement at high temperature was checked by using solid mixture of the selected metal oxide particle and NiO based oxygen carrier and the reactivity was measured and investigated using batch type fluidized bed. The solid mixture of Co3 O4 /CoAl2 O4 (10%) and OCN706-1100 (90%) showed higher fuel conversion, higher CO2 selectivity and lower CO concentration than OCN 706-1100 (100%) case. Consequently, we could conclude that improvement of reduction reactivity at high temperature range by adding some Co3 O4 based oxygen carrier is feasible.